Nationalism and terror : Ante Pavelic and Ustashe terrorism from fascism to the Cold War - Adriano, Pino; Cingolani, Giorgio (Central European University Press, 2018)
This book covers the full story of the Ustasha, a fascist movement in Croatia, from its historic roots up to its downfall. The two authors sought answers to questions that touch the heart of the issue: In what international context did Ustasha terrorism grow and develop? How could the movement settle to power and exterminate hundreds of thousands of innocents? Who was its leader, Ante Pavelić? A shrewd politician, able to exploit for his independent project Mussolini's imperial ambitions, Hitler's panGerman aims, the antiBolshevism of the Holy See and of the Western bloc? Or was he, consciousl.